2016
DOI: 10.1098/rsbl.2016.0066
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific variability of hindlimb length in the palmate newt: an indicator of population isolation induced by habitat fragmentation?

Abstract: Habitat fragmentation is one of the main drivers of global amphibian decline. Anthropogenic landscape elements can act as barriers, hindering the dispersal that is essential for maintaining gene flow between populations. Dispersal ability can be influenced by locomotor performance, which in turn can depend on morphological traits, such as hindlimb length (HLL) in amphibians. Here, we tested relationships between HLL and environmental variables-road types, forests and agricultural lands-among 35 subpopulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…There are currently few empirical studies assessing this theory by quantifying environmental fluctuations and their In general, travelling longer distances and travelling across a fragmented landscape requires enhancing traits such as higher movement abilities and correlated phenotypic attributes, e.g. different metabolic fuels, muscle development (Zera and Denno 1997), body shape (Hill et al 1999b), longer wings (Harrison 1980, Taylor and Merriam 1995, Zera and Denno 1997, longer legs (Trochet et al 2016b) or better orientation and navigation skills Perrin 2006, Merckx and. For example, a recent study found larger eyes in dispersing than in philopatric individuals of the bog fritillary Boloria eunomia (Turlure et al 2016).…”
Section: Direct Effects Of Fragmentation Featuresmentioning
confidence: 99%
“…There are currently few empirical studies assessing this theory by quantifying environmental fluctuations and their In general, travelling longer distances and travelling across a fragmented landscape requires enhancing traits such as higher movement abilities and correlated phenotypic attributes, e.g. different metabolic fuels, muscle development (Zera and Denno 1997), body shape (Hill et al 1999b), longer wings (Harrison 1980, Taylor and Merriam 1995, Zera and Denno 1997, longer legs (Trochet et al 2016b) or better orientation and navigation skills Perrin 2006, Merckx and. For example, a recent study found larger eyes in dispersing than in philopatric individuals of the bog fritillary Boloria eunomia (Turlure et al 2016).…”
Section: Direct Effects Of Fragmentation Featuresmentioning
confidence: 99%
“…Interestingly, while matrix type did not change movement propensity, it influenced movement strategies through its dependencies on local conditions and individual phenotypes. In amphibian species, large body size and legs increase movement capacity by improving locomotion performance both in terms of endurance and speed (Goater et al 1993, Stevens et al 2004, Trochet et al 2016, 2019. In this study, larger toads had a higher rate of movement whatever the local conditions or the type of matrix.…”
Section: Accepted Ar Ticlementioning
confidence: 52%
“…Ronce and Clobert 2012 for dispersal syndrome). For instance, dispersing individuals can display enhanced locomotor skills such as longer wings in flying species or longer legs in terrestrial species (Legrand et al 2015, Trochet et al 2016. A larger body size also enhances locomotion efficiency and has been associated with dispersal propensity because it reduces energetic costs of movements (Stevens et al 2004(Stevens et al , 2014).…”
Section: Accepted Ar Ticlementioning
confidence: 99%
“…Brady et al (2019) found that adult frogs in roadside ponds were more fecund, larger, and had elevated jumping performance, potentially due to roadside ponds being warmer due to the open canopy and having higher dissolved oxygen than woodland ponds, increasing growth. Palmate newts (Lissotriton helveticus) in had difference in hindlimb lengths in different environments, with selection toward less mobile short-legged newts in populations in areas with high road densities and mortalities due to higher mortality of more mobile long-legged newts, while populations in forests or from ponds close to other water bodies were long-legged (Trochet et al 2016).…”
Section: Effects Of Fragmentation Landscape Change and Accessibility ...mentioning
confidence: 99%